Adaptation and Flexibility of Residential Spatial Planning to the Functions of Home-Based Industries in Small Industrial Settlements - Suciati Permata (Ikatan Peneliti Lingkungan Binaan Indonesia, 2026)
Small-Scale Industrial Settlements or Perkampungan Industri Kecil (PIK) are areas that have developed through the integration of residential and home-based industrial functions, giving rise to a need for adaptive and flexible spaces. The lack of responsive spatial planning in this context often leads to problems such as overcrowding, a decline in environmental quality, and conflicts of function between living and working areas. This study identifies patterns of spatial adaptation in accommodating home-based industrial activities, analyses factors influencing spatial flexibility, evaluates the impact of spatial transformation on residents’ well-being, and formulates flexibility-based design strategies. The research methodology employs a mixed-methods approach (qualitative and quantitative), utilizing field observation, interviews, and spatial analysis. The findings indicate that the separation of spatial functions (vertical, horizontal, or integrated) is influenced by the type of business, land area, and socio-economic conditions. Flexible housing designs have been shown to enhance production efficiency and living comfort. This study contributes by providing a flexible housing design model and recommendations for adaptive spatial planning policies for the PIK area.